COMPARISON OF RICE FARMING INCOME WITH CORN AND WATERMELON FARMING IN SUBAK PANGYANGAN PANGYANGAN VILLAGE, PEKUTATAN DISTRICT - Ni Luh Putu Sindi Asih; Made Antara; Gede Mekse Korri Arisena (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
Subak Pangyangan is one of the subaks that still rely on the cultivation of food crops to lift their family's economy, where rice plants are still a food crop that is widely cultivated compared to other crops including corn and watermelon, so the corn and watermelon plants in Subak Pangyangan are Opoortunity Cost or